Creative Problem-Solving in Countries East and West Some Organizational Implications - Clapp, Ray; Ruckthum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Creativity and creative problem-solving are supported by two different cognitive styles, one concerned with adaption (doing things better), and the other with innovation (doing things differently). The current preoccupation with innovation would appear to favour western countries where a more innovative cultural bias exists. Furthermore, countries from the East would appear disadvantaged due to a similar bias towards adaption. However, organisations to sustain success need a diversity of style irrespective of the significance of any social or organisational leadership bias towards a single style. The pursuit of a dominant single style, be it adaption or innovation, leads to a diminishing organisational performance albeit by different routes.